The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s00520-018-4268-0
|View full text |Cite
|
Sign up to set email alerts
|

Ongoing ostomy self-care challenges of long-term rectal cancer survivors

Abstract: The majority of RC survivors reported ostomy-related self-care challenges, and 31% experienced problems across multiple domains of ostomy self-care. In addition, most survivors reported significant physical challenges that could lead to ostomy-related disability. Although the participants surveyed had access to ostomy care nurses, the care gaps we found suggest that additional work is needed to understand barriers to ostomy care, reduce unmet needs, and improve well-being among this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
58
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 36 publications
(31 reference statements)
4
58
0
5
Order By: Relevance
“…Regarding studies focussed on self‐care maintenance behaviours, investigators have studied compliance with the ostomy and pouching system (Bulkley et al., 2018; Ran et al., 2016; Sun et al., 2013) and dietary adjustment (Sun et al., 2013). Studies attributable to self‐care monitoring behaviours have been focussed on monitoring ostomy aspects, such as leakage (Bulkley et al., 2018) and dietary intake (de Oliveira, Boroni Moreira, Pereira Netto, & Gonçalves Leite, 2018). Regarding self‐care management, investigators have studied how ostomy patients deal with ostomy complications (Cheng, Meng, Yang, & Zhang, 2013; Vonk‐Klaassen et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding studies focussed on self‐care maintenance behaviours, investigators have studied compliance with the ostomy and pouching system (Bulkley et al., 2018; Ran et al., 2016; Sun et al., 2013) and dietary adjustment (Sun et al., 2013). Studies attributable to self‐care monitoring behaviours have been focussed on monitoring ostomy aspects, such as leakage (Bulkley et al., 2018) and dietary intake (de Oliveira, Boroni Moreira, Pereira Netto, & Gonçalves Leite, 2018). Regarding self‐care management, investigators have studied how ostomy patients deal with ostomy complications (Cheng, Meng, Yang, & Zhang, 2013; Vonk‐Klaassen et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, the results of those studies are inconsistent. For example, one study (Goldblatt et al., 2018) found that younger age is associated with better self‐care in terms of attaining independent stoma management, but another study (Bulkley et al., 2018) found that younger age was associated with more challenges in ostomy self‐care. Regarding gender, males have been found to perform better ostomy self‐care in terms of more independence in stoma care at discharge after surgery (Goldblatt et al., 2018), but another study found no statistically significant relationship between self‐care and gender (Bulkley et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Perioperatively for patients about to have a olostomy, doctors, nurses, and others' words are not as convincing as those of an Ostomy visitor. Only when patients see with there own eyes that people with an ostomy can lead happy lives after the same surgey can they believe that the ostomy surgey is not so very horrible [5]. Communication is a founding principle of nursing and is essential in order to give patient centered care which is safe and effective.…”
Section: Discussionmentioning
confidence: 99%